Molecular Diagnostics for Melanoma Methods and Protocols - Thurin, Magdalena; Marincola, Francesco M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
In Molecular Diagnostics for Melanoma: Methods and Protocols, expert researchers and clinicians in the field of melanoma provide updated information on biomarkers and assays for diagnosis, prognosis, and assays predicting response to treatment for routine testing. The focus of the volume is on biomarkers with established clinical validity rather than those on early discovery stage.  With additional in-depth discussion of the molecular biology and pathology of melanoma, treatment options in adjuvant and metastatic setting, and implications of biomarker testing for clinical management of melanoma patients.   Written in the highly successful Methods in Molecular Biology series format, chapters include extensive introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Comprehensive and practical, Molecular Diagnostics for Melanoma: Methods and Protocols seeks to provide both clinicians and scientists with technical information and extensive background information on the wide ranging approaches available in the field of diagnostics of melanoma.
Novel Insights/translational Implication from the Emerging Biology of Melanoma -- Emerging Clinical Issues in Melanoma in the Molecularly Targeted Era -- Integrating Molecular Biomarkers Into Current Clinical Management In Melanoma -- Advances in Adjuvant Therapy: Potential for Prognostic and Predictive Biomarkers -- Immunologic Monitoring of Cancer Vaccine Trials Using the ELISPOT Assay -- Markers for Anti-Cytotoxic T-lymphocyte Antigen 4 (CTLA-4) Therapy in Melanoma -- Marker Utility for Combination Therapy -- Assaying for BRAF V600E in Tissue and Blood in Melanoma -- Selecting Patients for KIT Inhibition in Melanoma -- Detecting Mechanisms of Acquired BRAF inhibitor Resistance in Melanoma -- Current Status of Diagnostic and Prognostic Markers in Melanoma -- Chromosomal Copy Number Analysis in Melanoma Diagnostics -- Construction and Analysis of Multi-Parameter Prognostic Models for Melanoma Outcome -- Immunohistochemical Diagnostic and Prognostic Markers for Melanoma -- Lymphatic Invasion as a Prognostic Biomarker in Primary Cutaneous Melanoma -- Tumor Infiltrating Lymphocytes and Their Significance in Melanoma Prognosis -- Pathological Staging of Melanoma -- Genotyping of Human Leukocyte Antigen (HLA) Ancestral Haplotypes as Prognostic Marker in Cancer Using PCR Analysis -- B7-H Abnormalities in Melanoma and Clinical Relevance -- Melanoma Susceptibility Genes and Risk Assessment -- Clinical, Pathologic, and Imaging Features, and Biological Markers of Uveal Melanoma -- A Prognostic Test to Predict Risk of Metastasis in Uveal Melanoma Based on a 15-Gene Expression Profile -- Molecular Karyotyping for Detection of Prognostic Markers in Fine Needle Aspirate Biopsy Samples of Uveal Melanoma -- ERBB4 Mutation Analysis: Emerging Molecular Target for Melanoma Treatment -- Epigenetic Markers of Prognosis in Melanoma -- Isolation of Melanoma Cell Subpopulations Using Negative Selection -- Circulating Tumor Cells as Prognostic Biomarkers in Cutaneous Melanoma Patients -- Detection of Chondroitin Sulfate Proteoglycan 4 (CSPG4) in Melanoma -- Targeting Damage Associated Molecular Pattern Molecules (DAMPs) and DAMP Receptors in Melanoma -- The Clinical Use of PET/CT in the Evaluation of Melanoma -- Immune System Functional Pathway Analysis Using Single Cell Network Profiling (SCNP): A Novel Tool in Cancer Immunotherapy -- Quantitative and Spatial Image Analysis of Tumor and Draining Lymph Nodes Using Immunohistochemistry and High Resolution Multispectral Imaging to Predict Metastasis -- COLD-PCR Enriches Low-Level Variant DNA Sequences and Increases the Sensitivity of Genetic Testing -- Isolation of Circulating MicroRNAs from Microvesicles found in Human Plasma -- Detection of Circulating Tumor Cells by Photoacustic Flowmetry -- Statistical Design and Evaluation of Biomarker Studies -- Tissue Resources for Clinical Use and Marker Studies in Melanoma.
Keywords: Cancer research; Oncology .; Cancer Research; Oncology